2010
DOI: 10.1021/jm100070n
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of 8-Oxoadenine Derivatives as Toll-like Receptor 7 Agonists Introducing the Antedrug Concept

Abstract: Systemic administration of a Toll-like receptor 7 (TLR7) agonist is effective to in suppressing Th2 derived inflammation, however systemic induction of various cytokines such as IL-6, IL-12, and type I interferon (IFN) is observed. This cytokine induction would be expected to cause flu-like symptoms. We have previously reported adenine compounds (3, 4) as interferon inducing agents acting as TLR7 agonists. To identify potent anti-inflammatory compounds without systemic side effects, a labile carboxylic ester a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 20 publications
1
44
0
Order By: Relevance
“…Stimulation of TLR7 modulates many of the end points associated with allergy in disease models including suppression of goblet cell hyperplasia, reduction in Th2 cytokines, lung eosinophilia, lung inflammation, and Ag-specific IgE (12)(13)(14)(15)(16)(17)(18). These data strongly support the concept of developing a TLR7 agonist to treat allergic disease, although current TLR7 agonists, used clinically in nonallergic indications, have side effects.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…Stimulation of TLR7 modulates many of the end points associated with allergy in disease models including suppression of goblet cell hyperplasia, reduction in Th2 cytokines, lung eosinophilia, lung inflammation, and Ag-specific IgE (12)(13)(14)(15)(16)(17)(18). These data strongly support the concept of developing a TLR7 agonist to treat allergic disease, although current TLR7 agonists, used clinically in nonallergic indications, have side effects.…”
mentioning
confidence: 66%
“…TLR7 antedrugs were rapidly metabolized in vivo (16,22) and short-term exposure of a TLR7 agonist was sufficient to induce IFN-a (22). Therefore, if the efficacy of an antedrug is linked to its ability to induce IFN-a, which itself has a short biological t 1/2 , then IFN-a has to induce effects that outlive its pharmacokinetic exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potency was greater than that observed on NF-kB-dependent reporter gene expression in TLR7-expressing HEK293 (Table I). To explore the factors playing a key role in the suppression, we determined whether type I IFN was involved in the inhibition of the Th2 cytokine production, as a TLR7 agonist is a powerful inducer of type I IFN (19). Results gained using splenocytes from IFN-a/bR 2/2 mice showed that, although rIFN-a inhibited IL-5, IL-13, and IFN-g production in murine splenocytes from wild-type mice in a dose-dependent manner, the suppression was completely lost in splenocytes from IFN-a/bR 2/2 mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported the synthesis and biological evaluation of antedrug TLR7 agonists, which are designed for rapid metabolism to a product with substantially reduced activity (19,20). Such compounds have the advantage over a metabolically stable TLR7 agonist by avoiding induction of potentially harmful systemic cytokine production.…”
mentioning
confidence: 99%